Peran Pembangunan Infrastruktur terhadap Ketimpangan Ekonomi Antarwilayah di Indonesia - Tatan Sukwika (Jurnal Wilayah dan Lingkungan, 2018)
Infrastructure disparity is considered as one of the factors that enhances economic inequality between regions. In the Indonesian context, the issue is interesting to be examined, especially the government is currently encouraging infrastructure development in various regions in Indonesia.This study aims at analyzing the dynamics of infrastructure and economic inequalities between regions (provinces) in Indonesia and examining the relationship between the two. This research employs several methods, namely Williamson Index, Klassen typology, and correlation and regression analyses. These methods are to provide an adequate scope of analysis to investigate trends and linkages of infrastructure development and economic imbalances between provinces in Indonesia. The study results find that the economic gap (in term of GRDP per capita) among the provinces in Indonesia was relatively high during the period 2011-2015. It was confirmed by the value of Williamson Index at 0.7 points. The relatively high rate of the gap was mostly associated with the infrastructure gap among the provinces. Strong positive correlation between the gap of GRDP per capita and of infrastructure among provinces. This delivers a strong message to the government to accelerate equal development programs proportionally in lagging regions in order to reduce development bias to more developed regions.